Upaya Penanganan Pembiayaan Mudharabah Bermasalah Di KSPS BMT Logam Mulia Klambu Grobogan - Tyas, Lu’lua Nur Rizkianing; Arifin, Jaenal (MALIA: Journal of Islamic Banking and Finance, 2020)
According to Saeed Mudharabah Financing Practices will encounter many problems in Islamic financial institutions, one of which is non-performing financing. This study seeks to describe the practice of mudharabah financing and the efforts to handle problematic mudharabah financing at KSPS BMT Logam Mulia. This study uses a qualitative method with a field research approach. To track data, researchers conducted observations and interviews as well as documentation according to the themes discussed. The informants selected by the researchers were managers and employees of the KSPS BMT Logam Mulia Klambu to conduct interviews in the data search process. First, the practice of mudharabah financing at KSPS BMT Logam Mulia Klambu runs as the mudharabah practice in sharia financial institutions, both banks and Islamic cooperatives. Second, the settlement of problematic mudharabah financing. KSPS BMT Logam Mulia prioritizes the principle of kinship and tries to avoid collateral execution or legal channels.